Evaluation of Sociodemographic Factors among Diabetic Patients with Urinary Tract Infections in Kisii Referral Hospital, Kenya - Vincent M. Mageto; Oliver W. Mbuthia; Caroline J. Ngetsa; Dinah O. Moraa; Erick O. Okoyo; Scholastica G. Mathenge; Wachuka G. Njoroge (International Journal of Microbiology)
People with noninsulin-dependent diabetes mellitus are prone to urinary tract infections. There is a wide gap of information in developing countries regarding the sociodemographic factors linked to UTI among diabetics and the gender disparity among the same. Sociodemographic factors differ with geographical location and many other factors, and this makes them an important aspect that can influence the social burden of UTI among diabetics. The objective of this study was to determine the association between sociodemographic factors and UTI among diabetics. The study was carried out in the Kisii Teaching and Referral Hospital in Kenya. One hundred and eighty diabetic patients were enrolled in cross-sectional study design. Clean-catch midstream urine was collected from all participants and cultured in cysteine lactose electrolyte deficient agar for bacterial isolation. Classification of a positive culture for urinary tract infection was based on more than 100,000 (≥105) colony-forming units of a single bacterial species. The data were analyzed using frequencies, chi-square (p<0.05), and logic regression with the help of the Statistical Package for the Social Sciences (SPSS) version 20 to find the odds ratio. One hundred and seven participants were male (59.4%), and 73 (40.6%) were female. The majority of the participants were between the age of 55 and 59 years old (77.2%), and 125 participants (69.4%) had attained tertiary education as the highest level of education. The overall prevalence of urinary tract infections was 20.6% with 37 participants testing positive for urinary tract infection. Age was found to have a significant association with urinary tract infection (p=0.002) while gender (p=0.45) and level of education (p=0.11) showed no significant association with urinary tract infections among diabetic patients. These findings suggest that age was the biggest association factor that influenced urinary tract infections among diabetic patients.